ANALISIS SEKTOR EKONOMI UNGGULAN DI KABUPATEN BANYUWANGI - Nurul Inayah, Nur Anim Jauhariyah (MALIA, 2016)
This study aimed to analyze the leading economic sector in Banyuwangi. The analysis used in this research is the analysis Klassen Typology, Location Quotient (LQ) and Shift Share. 1) The results of the analysis Klassen Typology a) advanced and rapidly growing sector (sector prima) is the agricultural sector, this sector should receive more attention from the local government to develop; b) advanced but depressed sector (Sector Potential) is the Mining and Quarrying sector, and Financial Sector, rentals, and service companies; c) the potential for Emerging Sectors is the construction sector; Electricity, gas and water supply; and Processing Industry; d) sector is lagging behind in Banyuwangi Trade, Hotels and Restaurants; Transportation and Communications; and Services. 2) Calculation Component competitive advantage by using the Shift-share analysis of classical generate competitive advantage value of Rp. 1.153.609.882.000- or 1,154 trillion rupiah, or 14.32 percent. This suggests that the resulting competitive advantage will increase economic development Banyuwangi; 3) the traditional sector (primary-farm) is more potent than other sectors. Leading sectors are the sectors that have a value LQ> 1 consists of: a) Agriculture; b) mining and quarrying; c) Financial services, leasing, and business services. The agricultural sector is a sector that still plays an important role and potential for economic growth in Banyuwangi.